Parents training parents: Lessons learned from a study of reciprocal imitation training in young children with autism spectrum disorder. (August 2019) - Hall, Trevor A; Mastel, Sarah; Nickel, Robert; Wainer, Allison
Parent-mediated interventions are cost-effective ways to increase access to appropriate treatment services to children with autism spectrum disorder. We aimed to engage parents working as partners within rural autism identification teams to facilitate prompt initiation of autism-specific treatment services and expand the amount of treatment available to young children with autism spectrum disorder. To do this, we sought to employ a two-phase training approach: (Phase 1) train parents to fidelity in an evidence-based parent-mediated intervention (reciprocal imitation training), and (Phase 2) evaluate the extent to which parents could effectively coach other parents of newly diagnosed children to implement reciprocal imitation training with their child. We experienced several unexpected barriers to completing all aspects of the Phase 1 training workflow. This led us to pivot toward a process evaluation. We used qualitative interviewing with our partner parents to systematically identify barriers and enhance the likelihood for successful future efforts at such an approach. The lessons we learned and recommendations for others attempting this type of research are presented.